THEOREMS IN QURAN ABOUT THE CREATION OF INSECTS AND ITS DIVERSITY IN TAMAN UNDAAN SURABAYA - Ain, Nurul (http://jagadalimussirry.com/, 2019)
In the Al-quran there are many verses that explain the animals that exist in this universe, one of which is about Insect. The research on Insect diversity around the Surabaya Undaan Park aims to describe the diversity of Insects and compare the number of members of each order in the Insect class around the Surabaya Undaan Park and look for their relevance to the Qur'anic proposition about the creation of Insects. The method used in this research assignment was observation, which was to go directly to the field to catch Insects in 5 plots in the vicinity of Surabaya Undakan Park with 4 repetitions in each plot, then collect data to be identified. Based on the results of observations, collection and identification, it can be found that there are various Insects in the area. This was evidenced by the discovery of various orders from Insectas, among others: Order Lepidoptera, Order Odonata, Order Hymenoptera, Order Diptera, and Order Orthoptera. Comparison of the number of species from each order is different. The most dominant number of species is in the order of Lepidoptera which was then followed by the order Hymenoptera.